Contractor's perspective on the impact of Covid-19 on construction industry / Noor Anisah Abdullah ... [et al.] - Abdullah, Noor Anisah; Mohamad Daud, Muhammad Ariff Danial; Mohamed Yusof, Nur Fatiha; Mohd Noor, Siti Nur Aishah (2022)
The World Health Organization (WHO) has declared COVID-19 a pandemic, forcing most of the country to go into lockdown. COVID-19 has caused widespread economic depression, forcing many businesses in various sectors, including the construction industry, to close down. As a result of the Malaysian government enforcing a Movement Control Order (MCO) to break the chain of COVID-19, the construction industry, without exception, is dealing with a slew of issues. It has a significant impact on the construction industry. Contractors are dealing with some difficulties as construction costs continue to increase as a result of workplace safety and health regulations, project suspension and termination, and productivity loss. Therefore, the aim of this research is to study the impact of COVID-19 pandemic outbreak on the construction industry in Malaysia based on the contractor's perspective. The study implied a quantitative method which is by distributing the questionnaires to the G1-G5 contractor's company in Klang Valley and all data are analysed by using SPSS. The result reveals that increment of the total cost of the project, increase in project duration, increase in material price and additional temporary accommodation for labour are the impact of COVID-19 on the construction industry during the COVID-19 pandemic outbreak. These findings can raise awareness among the contractor on the impacts of the pandemic outbreaks on the construction industry and help them to sustain the economic growth.